Pendampingan Bisnis Syariah pada Buruh Outsourcing Korban PHK di Kawasan Industri Manyar Gresik - Rahmawati, Lilik; Hakim, Abdul; Nurlailah, Nurlailah; Mustofa, Imam Ali (OECONOMICUS Journal of Economics, 2024)
The termination of employment (PHK) experienced by outsourced factory workers has a huge economic impact. Business assistance is an urgent matter for ex-layoff outsourced workers. Assistance for ex-layoff outsourced workers is carried out in the form of sharia business assistance. The mentoring model that is carried out is comprehensive. Comprehensive assistance is intended as assistance in all aspects of soft skills and hard skills of sharia business including creative and strategic thinking skills, effective communication, networking, analysis and decision-making skills, negotiation skills, time management, marketing management, financial management. Mentoring method with ABCD approach. This assistance is focused on the context of understanding and internalizing assets, potential, strength, and utilizing assets independently. Based on the analysis of the service team, the labor community actually has potential and character that can be developed so that it becomes income generating for the family. Several relevant businesses have been found that are tailored to their respective talents.